Pengembangan Aplikasi Desktop dalam Sistem Penyimpanan Otomatis Berbasis Robot dan Visi Komputer - Ahmad Sahro; Eko Mursito Budi (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2026)
Conventional storage and management processes in industrial sector are highly vulnerable to risks such as data entry errors, disorganized item placement, and time inefficiency due to human intervention. This phenomenon necessitates digitalization through precise and integrated automation. This research aims to design, implement, and test a application as the central control unit. The novelty of this study is the development of an application architecture that functions as a centralized supervision. This system not only manages the database but also coordinates storage workflows in real time, facilitates two-way industrial communication with FINS protocol, and performs position validation via visual detection. The research method applied is engineering research, using a research-by-project approach. The research stages are systematically, encompassing requirements identification, architecture design, program implementation, hardware integration, and comprehensive functionality testing. The application was developed using JavaFX, integrated with an Omron PLC and a computer vision module based on the YOLOv8 algorithm. Test results demonstrate that the application can perform administrative supervision functions, synchronize data communication with the PLC, and integrate the computer vision module with optimal stability. The implementation of this system is proven to minimize human error and improve the accuracy of goods placement through visual feedback mechanisms and centralized data.